Comparative perspectives on societal decline: Ibn Khaldun, Toynbee, and Hegel - Tahir, Zhilwan; Jalal Nori, Abdulwahed (Journal of History and Social Sciences, 2025)
This article explores the nuanced theories of societal decline offered by Ibn Khaldun, Arnold Toynbee, and G.W.F. Hegel, each providing unique insights into the mechanisms of civilizational collapse. Ibn Khaldun’s concept of Asabiyyah underscores the role of social cohesion in sustaining a society, arguing that its weakening leads to internal fragmentation and eventual decline. On the other hand, Toynbee focuses on the failure of ruling elites to creatively respond to external challenges, such as environmental changes or military threats, viewing their rigidity as a critical factor in societal disintegration. Hegel presents a more philosophical perspective, framing decline as an integral phase in the dialectical process, where contradictions within a society propel it toward transformation and higher stages of development. By examining the interplay of moral, cultural, and political forces in these theories, the article sheds light on how different frameworks conceptualize rise and fall dynamicsacross civilizations, offering a comparative lens to understand historical patterns and contemporary challenges.